2018
DOI: 10.1021/acs.jafc.8b05805
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell Catalytic Synthesis of Puerarin Monoesters and Analysis of Their Antioxidant Activities

Abstract: Puerarin, an important isoflavonoid from the edible root of Pueraria lobata, shows multiple bioactivities but suffers from low bioavailability. In this study, a new whole-cell catalytic method for acylation modification of puerarin was developed. Among the 12 strains tested, Aspergillus oryzae showed the highest catalytic activity and selectively catalyzed acylation of puerarin at the 6″-hydroxyl group. The organic solvents used significantly influenced the catalytic efficiency of the cells. In the green solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Each organic solvent has its unique molecular structure, and has unique interference with enzyme molecules. Therefore, bio-catalysts exhibit varying activity (Klibanov, 2001;Li et al, 2018), and the highest conversion medium is considered as the optimal reaction medium. Figure 3 shows effects of key factors such as catalyst dosage, reaction temperature, reaction time, and substrate dosage on the esterification of NH.…”
Section: Effect Of Different Lipases and Solvents On The Conversion Omentioning
confidence: 99%
See 2 more Smart Citations
“…Each organic solvent has its unique molecular structure, and has unique interference with enzyme molecules. Therefore, bio-catalysts exhibit varying activity (Klibanov, 2001;Li et al, 2018), and the highest conversion medium is considered as the optimal reaction medium. Figure 3 shows effects of key factors such as catalyst dosage, reaction temperature, reaction time, and substrate dosage on the esterification of NH.…”
Section: Effect Of Different Lipases and Solvents On The Conversion Omentioning
confidence: 99%
“…Various studies demonstrated that esterified flavonoids usually reach enhanced physiological activity and higher bioavailability compared to the original flavonoid compound (Kontogianni et al, 2001). Several flavonoids bioreactive substances, such as arbutin, naringin, puerarin, and dihydromyricetin, have previously been structurally modified to enhance their lipophilicity, thus expanding their application in the lipid environment (Kontogianni et al, 2001;Jiang et al, 2017;Li et al, 2018). For instance, acetylated arbutin can inhibit the bioactivity of melanoma cells and tyrosinase in B16 mice significantly more than unmodified arbutin (Jiang et al, 2017); puerarin has obvious antioxidant activity on erythrocyte hemolysis after the acylation catalyzed by the whole cell (Li et al, 2018); and the procyanidine of esterified grape seeds has antiproliferative and pro-apoptotic effects on PC3 prostate cancer cells (Chen and Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puerarin, also named 8-C-glucoside of daidzein (its chemical structure is shown in Figure 1A), is the major bioactive ingredient isolated from the root of the Pueraria lobata (Willd.) Ohwi, which is known as Gegen in Chinese traditional medicine [13]. Puerarin has been widely used to treat cardiovascular and cerebrovascular diseases in China [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since hydrophobic substrates can enter cells through passive diffusion [9], the solubility of substrates is generally considered a limiting factor, and the permeability of the cell membrane as a chemical (e.g., by adding detergents or solvents) and physical (e.g., temperature shock) treatments are used to improve the permeability of cell membranes, they may compromise cell integrity, spur the leakage of cellular components (e.g., diffusional loss of NAD(P)H), and affect downstream processes [10]. Given the attractive advantages of conventional water-miscible organic solvents, including their simple management, high solubility for various organic substances, and capacities to improve the enantio-selectivity and activity of biocatalysts [11,12], organic solvents have been used as "cosolvents" and "permeability enhancers" to stimulate substrate transfer across cells [7,10], but the choice and amount of added organic solvent are highly empirical and generally undesirable for large-scale applications [13]. In most single-enzyme whole-cell catalytic processes, dimethyl sulfoxide (DMSO) and methanol (MeOH) are commonly used as solubility enhancers to promote the biosynthesis of glycosides and hydrophobic compounds [14,15].…”
Section: Introductionmentioning
confidence: 99%